2008
DOI: 10.1124/jpet.108.140848
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cigarette Smoke-Induced Acute Inflammation in Multiple Strains of Mice and the Effect of a Matrix Metalloproteinase Inhibitor on These Responses

Abstract: The activities of proteases in the lung, specifically matrix metalloproteinases (MMPs), have been implicated in driving the inflammation and lung destruction observed in smokers with chronic obstructive pulmonary disease. Here, our aims were to compare the acute response with cigarette smoke exposure (CSE) in four mouse strains to identify common and distinguishing features and to assess the effect of an MMP inhibitor on this response. To do this, we exposed mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 23 publications
5
47
0
4
Order By: Relevance
“…Function class is intergenic (IG), intronic (IT), 5=-or 3=-untranslated region (UTR), coding synonymous (CSyn), or coding nonsynonymous (CNSyn). previously been observed upon CS exposure in BALB/cJ compared with C57Bl/6J mice (36). Accordingly, another study reported that BALB/cJ mice were the most susceptible mouse strains for developing CS-induced airway inflammation after 4 days of CS exposure compared with C57Bl/6J, 129S1/ SvlmJ, and C3H/HeJ mice, all also present in the present study (54).…”
Section: Discussionsupporting
confidence: 73%
“…Function class is intergenic (IG), intronic (IT), 5=-or 3=-untranslated region (UTR), coding synonymous (CSyn), or coding nonsynonymous (CNSyn). previously been observed upon CS exposure in BALB/cJ compared with C57Bl/6J mice (36). Accordingly, another study reported that BALB/cJ mice were the most susceptible mouse strains for developing CS-induced airway inflammation after 4 days of CS exposure compared with C57Bl/6J, 129S1/ SvlmJ, and C3H/HeJ mice, all also present in the present study (54).…”
Section: Discussionsupporting
confidence: 73%
“…PKF242-484 dose-dependently reduced neutrophilia in BALB/C mice after cigarette smoke exposure. Strangely, PKF242-484 had no effect in C57BL/6 mice, suggesting that the role of MMPs during smoke-induced acute neutrophil inflammation is strain dependent [47]. Ilomastat also effectively attenuated the inflammation and emphysema induced by cigarette smoke in mice [48].…”
Section: Dysregulation Of Mmps In Different Lung Disorders and Its Thmentioning
confidence: 97%
“…Further increasing smoke exposure to a maximum of five cigarettes did not significantly increase the 24 hr postexposure neutrophil count/percentage in BALF. Morris et al (2008) showed that exposure to at least four 1R3F cigarettes was needed to induce an increase in the proportion of BALF neutrophils in BALB/c mice. The discrepancy between these studies could result from differences in animal gender and the type of cigarettes used.…”
Section: Discussionmentioning
confidence: 99%